Preparation method of modified Ti-MSU molecular sieve catalyst, modified Ti-MSU molecular sieve catalyst and application of modified Ti-MSU molecular sieve catalyst

By modifying the Ti-MSU molecular sieve catalyst, using metal compounds and nanocarbon fiber modification, the problems of short catalyst life and low DCPDDO yield are solved, and higher catalyst service life and DCPDDO yield are achieved, and the safety and economicality of the process are improved.

CN119869608AActive Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311378316.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-24
Publication Date
2025-04-25
Estimated Expiration
2043-10-24

AI Technical Summary

Technical Problem

In the prior art, the catalyst life is short, the DCPDDO yield is low, the process safety is not high, the equipment is seriously corroded, and the amount of "three wastes" is large, which limits the production scale and output of dicyclopentadiene dioxide.

Method used

The modified Ti-MSU molecular sieve catalyst with metal compound modification and nanocarbon fiber/Ti-MSU as support is used to improve the hydrophobicity and coking resistance of the catalyst through silanization treatment, and is applied to the synthesis of DCPDDO.

Benefits of technology

While maintaining high DCPDDO product yield, it extends the service life of the catalyst, reduces equipment corrosion and "three wastes" amount, and improves the safety and economics of the process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004508650360000121
    Figure BDA0004508650360000121
Patent Text Reader

Abstract

The invention discloses a preparation method of a modified Ti-MSU molecular sieve catalyst, the modified Ti-MSU molecular sieve catalyst and application of the modified Ti-MSU molecular sieve catalyst. According to the invention, the active metal compound and the carbon nanofibers are introduced into the Ti-MSU catalyst, so that the modified Ti-MSU molecular sieve catalyst with better water resistance and coking resistance is obtained; the modified catalyst is used in the process of synthesizing DCPDDO through catalytic oxidation of DCPD, the conversion rate of DCPD and the selectivity of DCPDDO are high, and the catalyst is not prone to inactivation and can be operated for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of catalytic oxidation synthesis of organic epoxides and catalytic oxidation of olefins, and further to a preparation method of a modified Ti-MSU molecular sieve catalyst, a modified Ti-MSU molecular sieve catalyst and an application thereof. Background Art

[0002] DCPD (dicyclopentadiene) is an important component in the C9 fraction of ethylene cracking, accounting for about 17-28% of the C9 fraction. The epoxidation product of DCPD, DCPDDO (dicyclopentadiene dioxide), is a special alicyclic epoxy resin monomer. The consumption of alicyclic epoxy resin accounts for about 5% of the total consumption of epoxy resin. Among the numerous alicyclic epoxy resin products, dicyclopentadiene dioxide epoxy resin products are more eye-catching. Due to the high crosslinking density and high rigidity of DCPDDO and anhydride cured products, the cured products still have high strength when the heat deformation temperature is above 300°C, and the electrical properties at high temperatures are particularly excellent. Therefore, dicyclopentadiene dioxide epoxy resin is suitable for outdoor mutual inductor casting insulation, micro motor rotor casting material, high humidity resistant epoxy resin plastic sealing material, carbon fiber (or glass fiber) winding high-pressure container, high elastic modulus composite material, resin alloy mold, high temperature resistant laminated material, high strength weather-resistant fiberglass, anti-radiation coating, and aviation, aerospace, defense equipment manufacturing, etc., with good market prospects.

[0003] At present, the industrial production of dicyclopentadiene dioxide mainly adopts the peracetic acid method, firstly, glacial acetic acid is reacted with H2O2 to produce peracetic acid, then peracetic acid is used as an oxidant, and 98% concentrated sulfuric acid is used as a catalyst to catalyze the oxidation of dicyclopentadiene to produce dicyclopentadiene dioxide. The process is not safe, the equipment is severely corroded, the amount of "three wastes" is large, the production scale is small, and the output is not high, which limits its scope of use. The only dicyclopentadiene dioxide production enterprises in China are Jiangsu Taitel, Tianjin Jingdong and Yueyang Changde, etc., all of which adopt this process, and the production capacity and output are low. The dicyclopentadiene dioxide synthesis method in the research stage also has alkyl hydrogen peroxide method, sodium perborate method and sodium peroxydicarbonate method, H2O2 / heteropolyacid compound method, etc. The alkyl hydrogen peroxide method can obtain a relatively ideal yield, but the reaction temperature is high, the risk factor is large, the water content and the content of carbonyl by-products are strictly required, and the price of the oxidant and catalyst is expensive, and recycling is difficult. The sodium perborate method uses sodium perborate, which is relatively safe, as an oxidant to carry out epoxidation at room temperature. The process is safe and the operating conditions are simple, but the reaction time is long, there are many side reactions, and the yield is not high, only 50%. The sodium percarbonate method carries out epoxidation under ultrasonic radiation conditions, shortening the reaction time and increasing the yield of the target product, but the process is not economical and the yield is low, and there is still a long way to go before industrial production. In recent years, the H2O2 / heteropolyacid compound method has attracted widespread attention from researchers. It can be divided into homogeneous catalysts and heterogeneous catalysts according to its catalytic reaction mechanism. The homogeneous catalytic reaction is to add heteropolyacids or other salts into the reaction system. The catalytic activity is high and the process is simple, but the catalyst and the water phase are mixed together and cannot be separated, and cannot be recycled, making it difficult to scale up industrially; while the heterogeneous catalytic reaction achieves the recycling of the catalyst while maintaining a high catalytic efficiency, but there are still problems such as the easy shedding of heteropolyacids and the short life of the catalyst.

[0004] With the increasing demand for dicyclopentadiene dioxide, traditional dicyclopentadiene oxidation technology can no longer meet market demand, and it is imperative to research and develop new catalysts and reaction processes. Summary of the invention

[0005] In order to solve the problems in the prior art, the present invention proposes a preparation method of a modified Ti-MSU molecular sieve catalyst, a modified Ti-MSU molecular sieve catalyst and its application. The present invention synthesizes a modified Ti-MSU molecular sieve catalyst modified by a metal compound and using nanocarbon fiber / Ti-MSU as a carrier, which is applied to the synthesis of DCPDDO. While maintaining a higher DCPDDO product yield, a longer catalyst service life is obtained, which can solve the problems of short catalyst life and low DCPDDO yield in the existing DCPDDO synthesis process.

[0006] One of the objects of the present invention is to provide a method for preparing a modified Ti-MSU molecular sieve catalyst, comprising the following steps:

[0007] (1) dissolving the template in acidic water, adding a silicon source, a titanium source and an organic alcohol, heating and stirring the mixture, adding nano-carbon fibers and continuing to stir the mixture, crystallizing the mixture, separating the solid from the liquid, washing and drying the mixture to obtain Ti-MSU loaded on nano-carbon fibers;

[0008] (2) adding the Ti-MSU loaded on the nanocarbon fiber to an aqueous solution of a metal compound, stirring, solid-liquid separation, washing, drying, and then calcining in a protective atmosphere to obtain a modified Ti-MSU molecular sieve catalyst matrix;

[0009] (3) The modified Ti-MSU molecular sieve catalyst matrix is ​​subjected to silanization treatment with an organic silicon solution under a protective atmosphere, and after solid-liquid separation and drying, the modified Ti-MSU molecular sieve catalyst is obtained.

[0010] In the preparation method of the modified Ti-MSU molecular sieve catalyst of the present invention, preferably,

[0011] In step (1),

[0012] Dissolving the template in acidic water, and adding dropwise a mixture of a silicon source, a titanium source and an organic alcohol; and / or,

[0013] The template agent is selected from polyoxyethylene ether template agents; preferably, the template agent is selected from at least one of dodecyl polyoxyethylene ether, octadecyl polyoxyethylene ether or lauryl alcohol polyoxyethylene ether; and / or,

[0014] The pH value of the acidic water is 2 to 3, preferably the pH value of the water is adjusted with 0.5 to 1 mol / L hydrochloric acid or sulfuric acid, more preferably the pH value of the water is adjusted at 50 to 60°C; and / or,

[0015] The silicon source is selected from tetraalkyl silicate; preferably, the silicon source is selected from at least one of tetramethyl silicate, tetraethyl silicate or butyl orthosilicate; and / or,

[0016] The titanium source is selected from at least one of tetraalkyl titanate and titanium chloride salt; preferably, the titanium source is selected from at least one of tetrabutyl titanate, titanium trichloride or titanium tetrachloride; and / or,

[0017] The organic alcohol is selected from at least one of organic alcohols having 1 to 5 carbon atoms; preferably, the organic alcohol is selected from at least one of ethanol, isopropanol or isobutanol; and / or,

[0018] The nano-carbon fibers are formed by catalytic cracking reaction of the carbon-containing gas source using at least one carbon-containing gas source selected from CO, CH4, C2H6 or C3H8 as a raw material, and any single metal element or alloy of multiple elements in Group VIII of the periodic table as a catalyst; preferably, the temperature of the catalytic cracking reaction of the carbon-containing gas source is 600-1200°C, and the reaction time is 60-80min; and / or, the Group VIII element is selected from any single metal element or alloy of multiple elements selected from Fe, Co or Ni; and / or, the ratio of the number of atoms of the metal element in the catalyst to the number of carbon atoms in the carbon-containing gas source is 0.0001-0.0004:1.

[0019] The nano-carbon fibers prepared by the above method have an average outer diameter of 80-150 nm and an average fiber length of 13-20 um.

[0020] In the preparation method of the modified Ti-MSU molecular sieve catalyst of the present invention, preferably,

[0021] In step (1),

[0022] The temperature of the heating and stirring treatment is 50 to 60°C; and / or,

[0023] The heating and stirring treatment time is 12 to 36 hours; and / or,

[0024] The temperature of the continued stirring is 50-60°C; and / or,

[0025] The stirring time is 24 to 80 hours; and / or,

[0026] The temperature of the crystallization treatment is 130-180° C.; and / or the time of the crystallization treatment is 24-72 hours.

[0027] In the preparation method of the modified Ti-MSU molecular sieve catalyst of the present invention, preferably,

[0028] In step (1),

[0029] The molar ratio of the template to the silicon source is (0.1-1):1; and / or,

[0030] The molar ratio of silicon source to titanium source is 1:(0.02-0.1); and / or,

[0031] The molar ratio of silicon source to organic alcohol is 1:(10-15); and / or,

[0032] The molar ratio of silicon source to acidic water is 1:(150-200); and / or,

[0033] The molar ratio of the silicon source to the carbon nanofiber is 1:(5-15).

[0034] In the preparation method of the modified Ti-MSU molecular sieve catalyst of the present invention, preferably,

[0035] In step (2),

[0036] The metal compound is selected from at least one of MgO, MgCO3, Mg(OH)2, MoO3 or (NH4)2MoO4; and / or,

[0037] The aqueous solution of the metal compound is a saturated aqueous solution of the metal compound; preferably, the volume ratio of the Ti-MSU supported by the nano-carbon fiber to the saturated aqueous solution of the metal compound is 1:(1-4); and / or,

[0038] The stirring time is 12 to 48 hours; and / or,

[0039] The stirring temperature is room temperature; and / or,

[0040] The calcination temperature is 500-700°C; and / or,

[0041] The calcination time is 4 to 10 hours.

[0042] In the preparation method of the modified Ti-MSU molecular sieve catalyst of the present invention, preferably,

[0043] In step (3),

[0044] The organic solvent in the organosilicon solution is selected from benzene solvents, preferably at least one of toluene, ethylbenzene or isopropylbenzene; and / or,

[0045] The organosilicon in the organosilicon solution is selected from at least one of trimethylchlorosilane, triethylchlorosilane, dimethylphenylchlorosilane or hexamethyldisilazane; and / or,

[0046] The amount of organosilicon in the organosilicon solution is 20-80% of the weight of the modified Ti-MSU molecular sieve catalyst matrix; preferably, the organosilicon solution is a saturated organosilicon solution.

[0047] In the preparation method of the modified Ti-MSU molecular sieve catalyst of the present invention, preferably,

[0048] In step (3),

[0049] The temperature of the silanization treatment is 50 to 350° C.; and / or,

[0050] The silanization treatment time is 2 to 50 hours; and / or,

[0051] The drying temperature is 100 to 200°C; and / or,

[0052] The drying time is 12 to 24 hours.

[0053] In the present invention, the protective gas is a protective gas commonly used in the prior art, and is selected from at least one of nitrogen and an inert gas.

[0054] The second object of the present invention is to provide a modified Ti-MSU molecular sieve catalyst prepared by the preparation method provided in accordance with the first object of the present invention.

[0055] The catalyst of the present invention is a composite catalyst obtained by silanizing a modified Ti-MSU molecular sieve catalyst matrix; wherein the modified Ti-MSU molecular sieve catalyst matrix includes a Ti-MSU / nanocarbon fiber composite carrier and a metal compound loaded on the Ti-MSU / nanocarbon fiber and then calcined.

[0056] In the modified Ti-MSU molecular sieve catalyst of the present invention, preferably,

[0057] The catalyst has a three-dimensional mesoporous structure; preferably, the specific surface area of ​​the catalyst is 725 to 978 m 2 g -1 , pore diameter 3.75~4.75nm, pore volume 0.78~1.18cm 3 g -1 .

[0058] In the modified Ti-MSU molecular sieve catalyst of the present invention, preferably,

[0059] In the catalyst,

[0060] The molar ratio of silicon to titanium is 1:(0.02-0.1); and / or,

[0061] The molar ratio of silicon to carbon nanofiber is 1:(5-15).

[0062] The loading amount of the metal compound after calcination in the catalyst of the present invention can be measured by conventional testing methods in the art, or the loading amount of the metal compound after calcination can be obtained by the difference between the modified Ti-MSU molecular sieve catalyst matrix and the Ti-MSU loaded on nano-carbon fibers. Similarly, the mass change of the catalyst before and after silanization can be determined by the same method.

[0063] The third object of the present invention is to provide a modified Ti-MSU molecular sieve catalyst prepared by the preparation method as described in one of the objects of the present invention or the use of the modified Ti-MSU molecular sieve catalyst as described in the second object of the present invention in the epoxidation reaction of olefins; preferably, the use of the modified Ti-MSU molecular sieve catalyst in the epoxidation reaction of dicyclopentadiene to prepare dicyclopentadiene dioxide.

[0064] In the application of the present invention, preferably,

[0065] Under the action of catalyst, dicyclopentadiene and cumene hydroperoxide undergo epoxidation reaction in an organic solvent;

[0066] Preferably,

[0067] The organic solvent is a benzene substance, preferably cumene; and / or,

[0068] The molar ratio of dicyclopentadiene, cumene hydroperoxide and organic solvent is 1:(2-3):(6-11), preferably 1:(2.1-2.3):(8-10); and / or,

[0069] The temperature of the epoxidation reaction is 70 to 120° C.; and / or,

[0070] The epoxidation reaction pressure is 0.5 to 1.5 MPaG; and / or,

[0071] The total reaction material feed mass space velocity is 0.5~3h -1 and / or,

[0072] More preferably,

[0073] The epoxidation reaction temperature is 80 to 110° C.; and / or,

[0074] The epoxidation reaction pressure is 0.8-1.0 MPaG; and / or,

[0075] The total reaction material feed mass space velocity is 0.5~2h -1 .

[0076] The present invention has the following advantages:

[0077] (1) Compared with the peracetic acid method in the prior art, the method for olefin epoxidation of the present invention does not require the use of strong corrosive substances such as acids and alkalis, has low requirements on equipment materials, and has low equipment investment and maintenance costs;

[0078] (2) The modified Ti-MSU molecular sieve catalyst provided by the present invention is modified by metal compounds and nano-carbon fibers, and has stronger hydrophobicity and anti-coking properties. It not only has high DCPD conversion rate and DCPDDO selectivity, but also has a longer catalyst life and can be operated for a long period of time;

[0079] ⑶ The method of the present invention is not only suitable for the preparation of dicyclopentadiene dioxide by oxidation of dicyclopentadiene, but can also be widely used in various olefin epoxidation reactions, and has good industrial application prospects.

[0080] The endpoints and any values ​​of the scope disclosed in the present invention are not limited to the precise scope or value, and these scopes or values ​​should be understood to include values ​​close to these scopes or values. For numerical ranges, the endpoint values ​​of each scope, the endpoint values ​​of each scope and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article. Hereinafter, in principle, each technical solution can be combined with each other to obtain a new technical solution, which should also be regarded as specifically disclosed in this article. DETAILED DESCRIPTION

[0081] The present invention is described in detail below in conjunction with specific examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Some non-essential improvements and adjustments made to the present invention by those skilled in the art based on the content of the present invention still fall within the scope of protection of the present invention.

[0082] It should also be noted that the various specific technical features described in the following specific embodiments can be combined in any suitable manner without contradiction. To avoid unnecessary repetition, the present invention will not further describe various possible combinations.

[0083] In addition, the various embodiments of the present invention may be arbitrarily combined as long as they do not violate the concept of the present invention. The technical solutions thus formed belong to part of the original disclosure of this specification and also fall within the protection scope of the present invention.

[0084] The raw materials used in the examples and comparative examples, unless otherwise specified, are disclosed in the prior art, for example, they can be directly purchased or prepared according to the preparation methods disclosed in the prior art.

[0085] The carbon fiber used in the embodiment of the present invention: the nano-carbon fiber is made of carbon-containing gas source CH4 as raw material, and the element Co of Group VIII of the periodic table is selected as a catalyst. The ratio of the number of atoms of the metal element in the catalyst to the number of carbon atoms in the carbon-containing gas source is 0.0002:1, and the nano-carbon fiber is formed by catalytic cracking reaction of the carbon-containing gas source; preferably, the temperature of the catalytic cracking reaction of the carbon-containing gas source is 1000°C, and the reaction time is 70min.

[0086] Example 1

[0087] (1) At room temperature and under stirring, first dissolve 20.5 g of dodecyl polyoxyethylene ether (molecular weight 582.81) in 540 g of acidic water with a pH value of 2, then dropwise add a mixture of 30.4 g of tetramethyl silicate, 1.4 g of tetrabutyl titanate and 92 g of ethanol into the above solution, heat to 50 ° C, and stir for 12 h; pour into a 1000 mL reactor, add 12 g of nano-carbon fiber, and continue stirring for 24 h; heat to 130 ° C, crystallize for 24 h, filter to obtain a solid, wash with pure water until neutral, and dry at 80 ° C for 12 h to obtain Ti-MSU loaded with nano-carbon fiber;

[0088] (2) adding the obtained nanocarbon fiber-supported Ti-MSU to 1 volume of MgO saturated aqueous solution, stirring at room temperature for 12 h, filtering out the solid, washing with pure water until neutral, drying at 80 ° C for 12 h, and calcining at 500 ° C for 4 h under helium protection to obtain a Ti-MSU catalyst matrix modified with a metal compound and nanocarbon fiber as a carrier;

[0089] (3) In a 100 mL reactor, 20 g of the prepared Ti-MSU catalyst matrix was added, and 30 mL of a toluene solution containing 4 g of trimethylsilyl chloride was added. Under nitrogen protection, the reaction was stirred at 50 ° C for 2 h, and the reaction was terminated. After the material was naturally cooled, the solid catalyst was filtered out and dried at 100 ° C for 12 h to obtain a Ti-MSU / nanocarbon fiber composite catalyst modified with a metal compound treated by silanization.

[0090] Example 2

[0091] (1) At room temperature and under stirring, first dissolve 109.6g of octadecyl polyoxyethylene ether (molecular weight of about 770) in 648g of acidic water with a pH value of 3, then add a mixture of 41.7g of tetraethyl silicate, 1.6g of titanium trichloride and 144g of isopropanol dropwise into the above solution, heat to 55°C, and stir for 24h; pour into a 1000mL reactor, add 19.2g of nanocarbon fiber, and continue stirring for 48h; heat to 150°C, crystallize for 48h, filter to obtain a solid, wash with pure water until neutral, and dry at 80°C for 12h to obtain Ti-MSU loaded with nanocarbon fiber;

[0092] (2) adding the obtained nanocarbon fiber-supported Ti-MSU to a 2-fold volume of a saturated aqueous solution of MgCO3, stirring at room temperature for 24 h, filtering out the solid, washing with pure water until neutral, drying at 80°C for 12 h, and calcining at 600°C for 6 h under helium protection to obtain a Ti-MSU catalyst matrix modified with a metal compound and supported by nanocarbon fibers;

[0093] (3) In a 100 mL reactor, 20 g of the prepared Ti-MSU catalyst precursor was added, and 50 mL of ethylbenzene solution containing 4 g of triethylchlorosilane was added. Under nitrogen protection, the reaction was stirred at 150°C for 20 h, and the reaction was terminated. After the material was naturally cooled, the solid catalyst was filtered out and dried at 150°C for 16 h to obtain a Ti-MSU / nanocarbon fiber composite catalyst modified with a metal compound treated with silanization.

[0094] Example 3

[0095] (1) At room temperature and under stirring, first dissolve 72g of lauryl alcohol polyoxyethylene ether (molecular weight 1316) in 576g of acidic water with a pH value of 2, then add a mixture of 64.1g of butyl orthosilicate, 3.0g of titanium tetrachloride and 207.48g of isobutyl alcohol dropwise into the above solution, heat to 60°C, and stir for 36h; pour into a 1000mL reactor, add 24g of nano-carbon fiber, and continue stirring for 72h; heat to 160°C, crystallize for 60h, filter to obtain a solid, wash with pure water until neutral, and dry at 80°C for 12h to obtain Ti-MSU loaded with nano-carbon fiber;

[0096] (2) adding the obtained nanocarbon fiber-supported Ti-MSU to a 3-fold volume of a saturated aqueous solution of MoO3, stirring at room temperature for 36 h, filtering out the solid, washing with pure water until neutral, drying at 80°C for 12 h, and calcining at 650°C for 8 h under helium protection to obtain a Ti-MSU catalyst matrix modified with a metal compound and supported by nanocarbon fibers;

[0097] (3) In a 100 mL reactor, 20 g of the prepared Ti-MSU catalyst precursor was added, and 50 mL of cumene solution containing 4 g of dimethylphenylchlorosilane was added. Under nitrogen protection, the reaction was stirred at 300 ° C for 36 h, and the reaction was terminated. After the material was naturally cooled, the solid catalyst was filtered out and dried at 170 ° C for 20 h to obtain a Ti-MSU / nanocarbon fiber composite catalyst modified with a metal compound treated by silanization.

[0098] Example 4

[0099] (1) At room temperature and under stirring, first dissolve 219.2g of octadecyl polyoxyethylene ether (molecular weight of about 770) in 720g of acidic water with a pH value of 3, then dropwise add a mixture of 41.66g of tetraethyl silicate, 6.8g of tetrabutyl titanate and 138g of ethanol into the above solution, heat to 60°C, and stir for 24h; pour into a 1000mL reactor, add 36g of nanocarbon fiber, and continue stirring for 80h; heat to 180°C, crystallize for 72h, filter to obtain a solid, wash with pure water until neutral, and dry at 80°C for 12h to obtain Ti-MSU loaded with nanocarbon fiber;

[0100] (2) adding the obtained nanocarbon fiber-supported Ti-MSU to 4 times the volume of a saturated aqueous solution of (NH4)2MoO4, stirring at room temperature for 48 hours, filtering out the solid, washing with pure water until neutral, drying at 80°C for 12 hours, and calcining at 700°C for 10 hours under helium protection to obtain a Ti-MSU catalyst matrix modified with a metal compound and supported by nanocarbon fibers;

[0101] (3) In a 100 mL reactor, 20 g of the prepared Ti-MSU catalyst precursor was added, and 60 mL of ethylbenzene solution containing 4 g of hexamethyldisilazane was added. Under nitrogen protection, the reaction was stirred at 350 ° C for 50 h, and the reaction was terminated. After the material was naturally cooled, the solid catalyst was filtered out and dried at 200 ° C for 24 h to obtain a Ti-MSU / nanocarbon fiber composite catalyst modified with a metal compound treated by silanization.

[0102] The above embodiments of the present invention provide a metal compound modified Ti-MSU / nano carbon fiber composite catalyst, wherein the Ti-MSU catalyst has three-dimensional pore mesoporous characteristics (specific surface area 725-978m 2 g -1 , pore diameter 3.75~4.75nm, pore volume 0.78~1.18cm 3 g -1 ), Ti-MSU / nanocarbon fiber composite catalyst modified with metal oxides.

[0103] Comparative Example 1

[0104] The preparation method is basically the same as that of Example 4, except that:

[0105] In step (1), the step of loading nanocarbon fibers is not performed.

[0106] Comparative Example 2

[0107] The preparation method is basically the same as that of Example 4, except that:

[0108] The metal compound modification treatment in step (2) was not performed.

[0109] Comparative Example 3

[0110] The preparation method is basically the same as that of Example 4, except that:

[0111] The silanization treatment in step (3) was not performed.

[0112] Embodiments 5 to 20

[0113] The catalysts prepared in Examples 1 to 4 and Comparative Examples 1 to 3 were used to synthesize dicyclopentadiene dioxide in a 100 mL fixed bed reactor. The effects of temperature, pressure, material ratio and feed space velocity on the product were investigated in a continuous reaction process. The results are shown in Table 1.

[0114] The catalysts used in Examples 5 to 8 are provided by Example 1, the catalysts used in Examples 9 to 12 are provided by Example 2, the catalysts used in Examples 13 to 16 are provided by Example 3, and the catalysts used in Examples 17 to 20 are provided by Example 4; the catalysts used in Examples 21 to 23 are provided by Comparative Example 1, Comparative Example 2, and Comparative Example 3, respectively.

[0115] Table 1

[0116]

[0117] Embodiment 24

[0118] The modified Ti-MSU prepared in Example 4 was used as the catalyst, and the reaction temperature was 100°C, the reaction pressure was 1.0 MPaG, and the feed space velocity was 1.0 h -1 Under the conditions, DCPD, CHP and isopropylbenzene were introduced into a 100 mL fixed bed reactor at a molar ratio of 1:2.2:10 to undergo continuous epoxidation reaction. The effect of catalyst life on the reaction was investigated. The results are shown in Table 2.

[0119] Table 2

[0120] Catalyst life DCPD conversion rate DCPDDO selectivity h % % 24 100 100 240 99.9 100 480 99.8 99.9 720 99.8 99.8

[0121] Comparative Example 4

[0122] The commercially available Ti-MSU-1 molecular sieve was used as a catalyst as a comparative example. The experimental method was the same as that in Example 24. The effect of the catalyst life on the reaction was investigated. The results are shown in Table 3.

[0123] Table 3

[0124] Catalyst life DCPD conversion rate DCPDDO selectivity h % % 24 95.2 98.0 240 93.1 96.5 480 90.5 95.6 720 85.3 91.7

[0125] The Ti-MSU molecular sieve catalyst currently available on the market is used for DCPDDO synthesis. It has good initial activity, but as its service life increases, its catalytic activity decreases. The reason is that CHP (isopropylbenzene hydroperoxide) will decompose during the reaction to produce a certain amount of water and acid, which can easily cause the polymerization of the reaction products, resulting in blockage of the catalyst pores, cracking of the skeleton, and loss of titanium, which affects the catalytic performance of the catalyst.

[0126] The present invention synthesizes a Ti-MSU catalyst modified by a metal compound and using nano-carbon fibers as a carrier, and applies it to the synthesis of DCPDDO, thereby maintaining a higher DCPDDO product yield and obtaining a longer catalyst service life.

[0127] Comparative Example 5

[0128] Taking the catalysts in Comparative Examples 1-3 as comparative examples, the experimental method was the same as that in Example 24 to investigate the effect of catalyst life on the reaction. The results are shown in Table 4.

[0129] Table 4

[0130] catalyst Catalyst life DCPD conversion rate DCPDDO selectivity h % % Comparative Example 1 480 92.2 96.1 Comparative Example 2 480 91.7 96.8 Comparative Example 3 480 93.1 95.4

[0131] It can be seen from the above results that according to the catalyst preparation method provided by the present invention, nano-carbon fibers are used as carriers and modified with metal compounds, the water resistance of the catalyst is greatly improved and the service life of the catalyst is longer.

[0132] The present invention has been described in detail above in conjunction with specific implementations and exemplary examples, but these descriptions cannot be understood as limiting the present invention. Those skilled in the art understand that, without departing from the spirit and scope of the present invention, a variety of equivalent substitutions, modifications or improvements may be made to the technical solution of the present invention and its implementation methods, all of which fall within the scope of the present invention. The scope of protection of the present invention shall be subject to the attached claims.

[0133] All publications, patent applications, patents and other references mentioned in this specification are incorporated herein by reference. Unless otherwise defined, all technical and scientific terms used in this specification have the meanings conventionally understood by those skilled in the art. In the event of a conflict, the definition in this specification shall prevail.

[0134] When this specification uses the prefix "well-known to those skilled in the art", "prior art" or similar terms to introduce materials, substances, methods, steps, devices or components, etc., the objects introduced by the prefix cover those commonly used in the art when this application is filed, but also include those that are not commonly used at present but will become recognized in the art as being suitable for similar purposes.

[0135] In the context of the present specification, any matters or items not mentioned are directly applicable to those known in the art without any changes except those explicitly stated.

Claims

1. A method for preparing a modified Ti-MSU molecular sieve catalyst, characterized in that: The following steps are involved: (1) dissolving the template in acidic water, adding a silicon source, a titanium source and an organic alcohol, heating and stirring the mixture, adding nano-carbon fibers and continuing to stir the mixture, crystallizing the mixture, separating the solid from the liquid, washing and drying the mixture to obtain Ti-MSU loaded on nano-carbon fibers; (2) adding the Ti-MSU loaded on the nanocarbon fiber to an aqueous solution of a metal compound, stirring, solid-liquid separation, washing, drying, and then calcining in a protective atmosphere to obtain a modified Ti-MSU molecular sieve catalyst matrix; (3) The modified Ti-MSU molecular sieve catalyst matrix is ​​subjected to silanization treatment with an organic silicon solution under a protective atmosphere, and after solid-liquid separation and drying, the modified Ti-MSU molecular sieve catalyst is obtained.

2. The method for preparing the modified Ti-MSU molecular sieve catalyst according to claim 1, characterized in that: In step (1), The template agent is selected from polyoxyethylene ether template agents; preferably, the template agent is selected from at least one of dodecyl polyoxyethylene ether, octadecyl polyoxyethylene ether or lauryl alcohol polyoxyethylene ether; and / or, The pH value of the acidic water is 2 to 3, preferably the pH value of the water is adjusted with 0.5 to 1 mol / L hydrochloric acid or sulfuric acid, more preferably the pH value of the water is adjusted at 50 to 60°C; and / or, The silicon source is selected from tetraalkyl silicate; preferably, the silicon source is selected from at least one of tetramethyl silicate, tetraethyl silicate or butyl orthosilicate; and / or, The titanium source is selected from at least one of tetraalkyl titanate and titanium chloride salt; preferably, the titanium source is selected from at least one of tetrabutyl titanate, titanium trichloride or titanium tetrachloride; and / or, The organic alcohol is selected from at least one of organic alcohols having 1 to 5 carbon atoms; preferably, the organic alcohol is selected from at least one of ethanol, isopropanol or isobutanol; and / or, The nano-carbon fibers are formed by catalytic cracking reaction of the carbon-containing gas source using at least one carbon-containing gas source selected from CO, CH4, C2H6 or C3H8 as a raw material, and any single metal element or alloy of multiple elements in Group VIII of the periodic table as a catalyst; preferably, the temperature of the catalytic cracking reaction of the carbon-containing gas source is 600-1200°C, and the reaction time is 60-80min; and / or, the Group VIII element is selected from any single metal element or alloy of multiple elements selected from Fe, Co or Ni; and / or, the ratio of the number of atoms of the metal element in the catalyst to the number of carbon atoms in the carbon-containing gas source is (0.0001-0.0004):

1.

3. The method for preparing the modified Ti-MSU molecular sieve catalyst according to claim 1, characterized in that: In step (1), The temperature of the heating and stirring treatment is 50-60°C; and / or, The heating and stirring treatment time is 12 to 36 hours; and / or, The temperature of the continued stirring is 50-60°C; and / or, The stirring time is 24 to 80 hours; and / or, The temperature of the crystallization treatment is 130-180° C.; and / or the time of the crystallization treatment is 24-72 hours.

4. The method for preparing the modified Ti-MSU molecular sieve catalyst according to claim 1, characterized in that: In step (1), The molar ratio of the template to the silicon source is (0.1-1):1; and / or, The molar ratio of silicon source to titanium source is 1:(0.02-0.1); and / or, The molar ratio of silicon source to organic alcohol is 1:(10-15); and / or, The molar ratio of silicon source to acidic water is 1:(150-200); and / or, The molar ratio of the silicon source to the carbon nanofiber is 1:(5-15).

5. The method for preparing the modified Ti-MSU molecular sieve catalyst according to claim 1, characterized in that: In step (2), The metal compound is selected from at least one of MgO, MgCO3, Mg(OH)2, MoO3 or (NH4)2MoO4; and / or, The aqueous solution of the metal compound is a saturated aqueous solution of the metal compound; preferably, the volume ratio of the Ti-MSU supported by the nano-carbon fiber to the saturated aqueous solution of the metal compound is 1:(1-4); and / or, The stirring time is 12 to 48 hours; and / or, The stirring temperature is room temperature; and / or, The calcination temperature is 500-700°C; and / or, The calcination time is 4 to 10 hours.

6. The method for preparing the modified Ti-MSU molecular sieve catalyst according to claim 1, characterized in that: In step (3), The organic solvent in the organosilicon solution is selected from benzene solvents, preferably at least one of toluene, ethylbenzene or isopropylbenzene; and / or, The organosilicon in the organosilicon solution is selected from at least one of trimethylchlorosilane, triethylchlorosilane, dimethylphenylchlorosilane or hexamethyldisilazane; and / or, The amount of organosilicon in the organosilicon solution is 20-80% of the weight of the modified Ti-MSU molecular sieve catalyst matrix; preferably, the organosilicon solution is a saturated organosilicon solution.

7. The method for preparing the modified Ti-MSU molecular sieve catalyst according to claim 1, characterized in that: In step (3), The temperature of the silanization treatment is 50 to 350° C.; and / or, The silanization treatment time is 2 to 50 hours; and / or, The drying temperature is 100 to 200°C; and / or, The drying time is 12 to 24 hours.

8. A modified Ti-MSU molecular sieve catalyst prepared by the preparation method according to any one of claims 1 to 7.

9. Use of a modified Ti-MSU molecular sieve catalyst prepared by the preparation method according to any one of claims 1 to 7 or a modified Ti-MSU molecular sieve catalyst according to claim 8 in an olefin epoxidation reaction; preferably in the preparation of dicyclopentadiene dioxide by the epoxidation reaction of dicyclopentadiene.

10. The use according to claim 9, characterized in that: Under the action of catalyst, dicyclopentadiene and cumene hydroperoxide undergo epoxidation reaction in an organic solvent; Preferably, The organic solvent is a benzene substance, preferably cumene; and / or, The molar ratio of dicyclopentadiene, cumene hydroperoxide and organic solvent is 1:(2-3):(6-11), preferably 1:(2.1-2.3):(8-10); and / or, The temperature of the epoxidation reaction is 70 to 120° C.; and / or, The epoxidation reaction pressure is 0.5 to 1.5 MPaG; and / or, The total reaction material feed mass space velocity is 0.5~3h -1 ; More preferably, The epoxidation reaction temperature is 80 to 110° C.; and / or, The epoxidation reaction pressure is 0.8-1.0 MPaG; and / or, The total reaction material feed mass space velocity is 0.5~2h -1 .

Citation Information

Patent Citations

  • Catalyst for oxidizing-synthesizing glutaric dialdehyde with cyclopentene and preparation method thereof

    CN101564686A

  • Preparation method of nitrogen titanium silicon-containing molecular sieve

    CN102219234A

  • Method for catalyzing olefin epoxidation reaction by using titanium-containing mesoporous molecular sieve

    CN112742444A

  • Magnesium-containing compound modified Ti-HMS / carbon nanofiber composite catalyst and preparation and application thereof

    CN113083358A

  • Production of alkylene oxide directly from alkane

    JP2009051769A